Downregulation of ERp57 expression is associated with poor prognosis in early-stage cervical cancer. (November 2013) - Chung, Hyunsoo; Cho, Hanbyoul; Perry, Candice; Song, Jaekyung; Ylaya, Kris; Lee, Heejeong; Kim, Jae-Hoon
Abstract Objective: We investigated the clinical significance of ERp57 in the progression of cervical cancer. Methods: mRNA and protein expression of ERp57 in cervical neoplasias were examined. Results: ERp57 mRNA expression was significantly decreased in cervical cancers. Immunohistochemistry revealed that ERp57 expression in 123 cervical cancers was down-regulated compared to cervical intraepithelial neoplasias or normal tissues (p < 0.001). Low ERp57 expression was significantly associated with worse overall survival (HR = 12.19, p = 0.018). Conclusions: Low ERp57 expression independently predicts a poor outcome for patients with cervical cancer, supporting the notion that ERp57 may be a promising novel cancer target.